Willingness to forgiveness as a predictor of mental health and psychological resilience of displaced persons from the zone of military conflict in Eastern Ukraine - Kravchuk, Svitlana Leontivna (Social Welfare: Interdisciplinary Approach, 2020)
The article is devoted to the problem the characteristics of willingness to forgiveness in displaced persons from the conflict zone. The concepts of forgiveness and psychological resilience are considered. The article examines the characteristics of willingness to forgiveness as a predictor of mental health and psychological resilience of displaced persons from the conflict zone. The presented findings should be taken into account by persons offering professional support for such group of persons.